Chemically delaminated free-standing ultrathin covalent organic nanosheets - Khayum, M. Abdul; Kandambeth, Sharath; Mitra, Shouvik; Nair, Sanoop B.; Das, Anuja; Nagane, Samadhan S.; Mukherjee, Rabibrata; Banerjee, Rahul (Angewandte Chemie-International Edition, 2016)
Covalent organic nanosheets (CONs) are a new class of porous thin two-dimensional (2D) nanostructures that can be easily designed and functionalized and could be useful for separation applications. Poor dispersion, layer restacking, and difficult postsynthetic modifications are the major hurdles that need to be overcome to fabricate scalable CON thin films. Herein, we present a unique approach for the chemical exfoliation of an anthracene-based covalent organic framework (COF) to N-hexylmaleimide-functionalized CONs, to yield centimeter-sized free-standing thin films through layer-by-layer CON assembly at the air-water interface. The thinlayer fabrication technique presented here is simple, scalable, and does not require any surfactants or stabilizing agents.

Water-in-acid gel polymer electrolyte realized through a phosphoric acid-enriched polyelectrolyte matrix toward solid-state supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Torris, Arun A. T.; Chandran, Nikhil M. K.; Nair, Sanoop B.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Sustainable Chemistry & Engineering, 2018)
A new concept of water-in-acid gel polymer electrolytes (GPEs) is introduced. The simple and scalable UV-light-assisted synthesis of a copolymer matrix possessing polyelectrolyte behavior, followed by swelling in minimally diluted H3PO4 (15.1 M/88 wt % aqueous solution), effects formation of a high proton-conducting, self-standing, and mechanically stable polyelectrolyte GPE (PGPE). Retention of high mechanical stability despite the presence of a large amount of liquid species makes it a promising candidate for replacing conventional GPEs. The high proton conductivity (9.8 X 10(-2) S cm(-1)) of the PGPE at an ambient temperature of 303 K is attributed to the high concentration of the conducting species present in the polymer matrix. The PGPE-based polyaniline (PANI) supercapacitor device (PANI-1) with a mass loading of 1 mg cm(-2) exhibits a high specific gravimetric capacitance of 385 F g(-1) at a current density of 0.25 mA cm(-2). At the same current density, the PANI-5 device retains high gravimetric and areal capacitance values of 258 F g(-1) and 1288 mF cm(-2), respectively. The low equivalent series resistance value of 0.78 Omega (for the PANI-5 device) further proves the excellent electrode-electrolyte interface formed by the water-in-acid GPE. A 100% capacitance retention even after 9000 continuous charge-discharge cycles strongly indicates the feasibility of adopting water-in-acid GPEs in future supercapacitors.

Influence of hydrophilic/hydrophobic diols on the properties of polyurethane hydrogels: solvent-free one-pot synthesis - Divakaran, Anumon V.; Nair, Sanoop B.; Karambe, Shivani S.; Wadgaonkar, Prakash P.; Nair, Kiran Sukumaran; Badiger, Manohar V. (Journal of Materials Chemistry B, 2025)
Herein, we report the design and synthesis of bio-degradable porous polyurethane hydrogels by a green, solvent-free, one-pot technique that can withstand physiological mechanical loads and aid in tissue regeneration. The hydrophilic/hydrophobic nature of the hydrogel was tuned using diols such as polycaprolactone diol (PCL) and polycarbonate diol (PCD), in combination with polyethylene glycol (PEG, MW approximate to 4000 g mol-1), 4,4 `-methylene bis(cyclohexyl isocyanate) (H12MDI) and hexanetriol (HT), which served as crosslinking agents. The structural characterizations of the hydrogels were performed using FT-IR as well as 1H and 13C high resolution magic angle spinning nuclear magnetic resonance (HR-MAS) spectroscopy. The utilization of various diols in the synthesis of the hydrogels enabled precise control over crystallinity, pore sizes, and customization of mechanical and degradation properties. These hydrogels exhibited tensile strength in the range of 0.22-1.48 MPa, while their compressive strength varied from 0.92 to 29.3 MPa. In vitro degradation profiles in the presence and absence of the enzyme Amano lipase PS revealed that the degradation process is contingent upon the specific diol present in the hydrogel. Furthermore, preliminary in vitro biological experiments confirmed the biocompatibility of the gels, indicating their potential as suitable substrates for drug delivery applications. This diverse library of gels can be shaped into specific forms, highlighting their promising applications as scaffolds and implants in drug delivery systems and tissue engineering.